Hydriding-Induced Wall Stress Evaluation of a Prototype Four-Inch Short (FISH) Tritium Hydride Bed. (3rd April 2017) - Heroux, K. J.; Estochen, E. G.
Abstract: The hydriding-induced wall stress evaluation of a prototype Four-Inch SHort (FISH) tritium hydride bed revealed that the advanced design features do not result in additional strain on the process vessel walls during simulated operation. The maximum tensile wall stress measured at high hydrogen loadings (H/M > 0.7) was determined to be <40% of the ASME allowable limit for 316L stainless steel. Variation in wall stress with hydride loading was also examined via stepwise protium absorption and desorption. Minimal hydriding-induced wall stress was observed in the optimal operating range of the hydride material. The results described herein are in good agreement with previous studies on similar hydride storage beds without the advanced design features. Completed verification of ASME compliance for the FISH bed is a major milestone in its qualification for tritium service.